Stunting as a Risk Factor of Soil-Transmitted Helminthiasis in Children: A Literature Review - Fauziah, Nisa; Ar-Rizqi, Muhammad Abdurrahman; Hana, Sofia; Patahuddin, Nurul Mufliha; Diptyanusa, Ajib (Interdisciplinary Perspectives on Infectious Diseases, 2022)
As a high-burden neglected tropical disease, soil-transmitted helminth (STH) infections remain a major problem in the world, especially among children under five years of age. Since young children are at high risk of being infected, STH infection can have a long-term negative impact on their life, including impaired growth and development. Stunting, a form of malnutrition in young children, has been long assumed as one of the risk factors in acquiring the STH infections. However, the studies on STH infection in children under five with stunting have been lacking, resulting in poor identification of the risk. Accordingly, we collected and reviewed existing related research articles to provide an overview of STH infection in a susceptible population of stunted children under five years of age in terms of prevalence and risk factors. There were 17 studies included in this review related to infection with Ascaris lumbricoides, Trichuris trichiura, hookworm, and Strongyloides stercoralis from various countries. The prevalence of STH infection in stunted children ranged from 12.5% to 56.5%. Increased inflammatory markers and intestinal microbiota dysbiosis might have increased the intensity of STH infection in stunted children that caused impairment in the immune system. While the age from 2 to 5 years along with poor hygiene and sanitation has shown to be the most common risk factors of STH infections in stunted children; currently there are no studies that show direct results of stunting as a risk factor for STH infection. While stunting itself may affect the pathogenesis of STH infection, further research on stunting as a risk factor for STH infection is encouraged.